Dehydration of clastic sediments in subduction zones: Theoretical study using thermodynamic data of minerals - Ying Li; Hans‐Joachim Massonne; Arne Willner; Hong‐Feng Tang; Cong‐Qiang Liu (Island Arc, 2008)
Pseudosections for two sediments and one basalt calculated in the system K 2 O–Na 2 O–CaO–MgO–FeO–Fe 2 O 3 –Al 2 O 3 –TiO 2 –SiO 2 –H 2 O for the P–T range 10 to 35 kbar, 300 to 900°C give useful insights into the amount of H 2 O released from oceanic crust in subduction zones. In cold subduction zones (20 kbar–300°C to 35 kbar–500°C) hydrous minerals storing 3 to 4 wt% H 2 O are still present in metasediments at depths of 120 km. In the same environment, metabasite releases 1 wt% H 2 O in the depth range 100 to 120 km, but 4.5 wt% H 2 O is transported to greater depths. In hot subduction zones (300°C hotter than the cold subduction zone at 100 km depth), dehydration events of metasediments in the depth range 50 to 80 km correspond to the breakdown of chlorite and paragonite. In the calculations no further water is released at greater depths because the modal content of phengite, the only hydrous mineral phase at these depths, remains almost constant. For the same P–T path, metabasite shows continuous dehydration between 40 and 80 km releasing almost 3 wt% H 2 O. At 120 km depth less than 0.4 wt% of H 2 O remains. In an average modern subduction zone (∼6°C/km) most dehydration of sediments occurs at depths of 70 to 100 km and that of basalts at depths of 80 to 120 km. Only 1.3 wt% H 2 O in metasediments and 1.6 wt% H 2 O in metabasalt has the potential to be subducted to depths greater than 120 km. The dehydration behavior of sediments concurs with the generally held idea that subduction zone fluids are most effectively transported to great depths by cold subduction. In hot subduction zones, such as those characteristic of early Earth, most H 2 O carried by oceanic crust is liberated at depths less than 120 km and, thus, would not contribute to island‐arc magmatism.